Labeled as “drug-seeking”: nurses use harm reduction philosophy to reflect on mending mutual distrust between healthcare workers and people who use drugs - Febres-Cordero, Sarah; Shasanmi-Ellis, Rebecca O.; Sherman, Athena D. F. (Frontiers in Public Health, 2023)
Introduction Over 50 years of approaching drug use from the “War on Drugs” has led to ignoring the systemic structural and social determinants of health, enforced drug use stigma, and damaging stereotypes of people who use drugs or are labeled as “drug-seeking,” and sorely failed to support those needing assistance. On philosophy of harm reduction and power People who use drugs are often disenfranchised and pathologized by being labeled as “a drug addict,” which then serves as a rationalization for mistreatment by healthcare providers. This is in opposition to a harm-reduction approach. Harm reduction philosophy is an epistemic valuation necessary for drug use stigma and our moral obligation to reduce harm from interlocking systems of power that perpetuate harm. On drug-seeking, mistrust, and human rights We have encountered many clients who use drugs that report harmful interactions with healthcare providers. Harm reduction is an issue of health equity, social justice, and fundamental human rights. This paper presents three vignettes, the author’s experiences of being labeled as—and advocating for family members labeled as “drug-seeking.” Discussion To better serve as healthcare providers, workers must be equipped to work with people who use drugs and reinforce the social justice commitment against medical stigma, neglect, racism, and inadequate pain coverage and withdrawal treatment. Nurses and our epistemic lens can meet the challenge of complex intersectional issues affecting our use of power to develop more just and equitable health systems and advance our rebuilding of a trusting relationship with the people we serve.